51st AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2013
DOI: 10.2514/6.2013-81
|View full text |Cite
|
Sign up to set email alerts
|

Wake Instabilities behind Discrete Roughness Elements in High Speed Boundary Layers

Abstract: Computations are performed to study the flow past an isolated, spanwise symmetric roughness element in zero pressure gradient boundary layers at Mach 3.5 and 5.9, with an emphasis on roughness heights of less than 55 percent of the local boundary layer thickness. The Mach 5.9 cases include flow conditions that are relevant to both ground facility experiments and high altitude flight ("cold wall" case). Regardless of the Mach number, the mean flow distortion due to the roughness element is characterized by long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
41
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 21 publications
14
41
0
Order By: Relevance
“…For a k/δ k =0.44 element (Re kk =791), the roughness wake was found to be dominated by varicose mode instability driven by wall-normal shear, while sinuous mode instabilities (associated with lateral shear) were found to be relatively weaker. Results were in general agreement with previous numerical and experimental studies by Choudhari et al (2010Choudhari et al ( , 2013 and Kegerise et al (2012) on isolated diamond elements at Mach 3.5, where sinuous modes were found to experience greater amplification for shorter elements and varicose instability to become more dominant and drive the breakdown to turbulence for higher Re kk . In subsequent DNS studies on square elements by De Tullio & Sandham (2015) in a Mach 6 boundary layer, two main mechanisms responsible for the excitation of wake modes were described: a first one due to the interaction of the local reversed flow with external disturbances and a second one due to the interaction between the roughness wake and the different boundary layer modes.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…For a k/δ k =0.44 element (Re kk =791), the roughness wake was found to be dominated by varicose mode instability driven by wall-normal shear, while sinuous mode instabilities (associated with lateral shear) were found to be relatively weaker. Results were in general agreement with previous numerical and experimental studies by Choudhari et al (2010Choudhari et al ( , 2013 and Kegerise et al (2012) on isolated diamond elements at Mach 3.5, where sinuous modes were found to experience greater amplification for shorter elements and varicose instability to become more dominant and drive the breakdown to turbulence for higher Re kk . In subsequent DNS studies on square elements by De Tullio & Sandham (2015) in a Mach 6 boundary layer, two main mechanisms responsible for the excitation of wake modes were described: a first one due to the interaction of the local reversed flow with external disturbances and a second one due to the interaction between the roughness wake and the different boundary layer modes.…”
Section: Introductionsupporting
confidence: 91%
“…Below k/δ k =0.15, x tr is fixed at the corner due to the local destabilising effects and it is then shortened with increasing height, eventually asymptoting towards x tr ≈21±1mm (∼12δ k ). The effective transition length is of a similar order as that found under 'noisy' (highdisturbance) environmental conditions in Choudhari et al (2013) and Kegerise et al (2012). In their studies, the effective transition length induced by diamond elements was shown to be over 2.5 times longer under 'quiet' (low-noise) conditions, where the stability analysis of the element wake was based on N-factor calculations; the effect of environmental disturbance levels on x tr was further found to lead to even greater differences between 'quiet' and 'noisy' conditions for shorter elements, with the breakdown of the dominant modes associated to transition onset exhibiting a strongly nonlinear dependence on roughness height.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…Recently Wheaton & Schneider (2012 have carried out a set of experiments on roughness-induced transition at M = 6, reporting the first quantitative measurements of the roughness wake instability at hypersonic speeds. For the same Mach number, the numerical simulations of De Tullio & Sandham (2012) and Choudhari et al (2013) show that the roughness wake can sustain the growth of a number of different instability modes, the relative importance of which seems to depend on the specific flow conditions considered.…”
Section: Introductionmentioning
confidence: 93%
“…The shear layers in the wake of the roughness can sustain two types of instabilities: sinuous (sometimes called odd or antisymmetric), associated with the detached wall-normal shear layer; and varicose (or even/symmetric) modes concentrated near the regions of high spanwise shear at the sides. Varicose modes are usually more unstable [14,15] than sinuous modes, but it is not completely understood how they depend on the roughness geometry and flow conditions. Choudhari et al [6] found that, for lower roughness height, the sinuous modes were dominant, whereas the varicose modes became dominant for a roughness element with larger height.…”
mentioning
confidence: 99%